2018
DOI: 10.3344/kjp.2018.31.1.10
|View full text |Cite
|
Sign up to set email alerts
|

Allopregnanolone suppresses mechanical allodynia and internalization of neurokinin-1 receptors at the spinal dorsal horn in a rat postoperative pain model

Abstract: BackgroundTo identify a new strategy for postoperative pain management, we investigated the analgesic effects of allopregnanolone (Allo) in an incisional pain model, and also assessed its effects on the activities of the primary afferent fibers at the dorsal horn.MethodsIn experiment 1, 45 rats were assigned to Control, Allo small-dose (0.16 mg/kg), and Allo large-dose (1.6 mg/kg) groups (n = 15 in each). The weight bearing and mechanical withdrawal thresholds of the hind limb were measured before and at 2, 24… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
5
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(7 citation statements)
references
References 31 publications
2
5
0
Order By: Relevance
“…In the present study, we observed a rapid attenuation in the reemergence of mechanical allodynia within 1 h of injection on day 1. This is in agreement with previous studies that investigated the effects of allopregnanolone in animal models of neuropathic pain (Charlet et al, 2008;Meyer et al, 2008Meyer et al, , 2011Ocvirk et al, 2008;Kawano et al, 2011;Svensson et al, 2013;Afrazi and Esmaeili-Mahani, 2014;Fujita et al, 2018). Surprisingly, allopregnanolone treatment did not attenuate the return of mechanical allodynia on day 3 or 5 of hormone treatment.…”
Section: Discussionsupporting
confidence: 93%
See 2 more Smart Citations
“…In the present study, we observed a rapid attenuation in the reemergence of mechanical allodynia within 1 h of injection on day 1. This is in agreement with previous studies that investigated the effects of allopregnanolone in animal models of neuropathic pain (Charlet et al, 2008;Meyer et al, 2008Meyer et al, , 2011Ocvirk et al, 2008;Kawano et al, 2011;Svensson et al, 2013;Afrazi and Esmaeili-Mahani, 2014;Fujita et al, 2018). Surprisingly, allopregnanolone treatment did not attenuate the return of mechanical allodynia on day 3 or 5 of hormone treatment.…”
Section: Discussionsupporting
confidence: 93%
“…Allopregnanolone has been shown to have antinociceptive effects. Allopregnanolone attenuates diabetesinduced neuropathy (Afrazi and Esmaeili-Mahani, 2014), postoperative pain (Fujita et al, 2018), inflammatory pain (Charlet et al, 2008;Ocvirk et al, 2008), sciatic nerve ligation nociception (Meyer et al, 2008), and chemotherapyinduced nociception (Meyer et al, 2011). In the present study, we observed a rapid attenuation in the reemergence of mechanical allodynia within 1 h of injection on day 1.…”
Section: Discussionsupporting
confidence: 67%
See 1 more Smart Citation
“…35,39 Several studies have attempted to clarify the mechanism underlying the SP mediated responses and NK1 receptor internalization to investigate the feasibility of using NK1 receptor antagonist as a potential analgesics. 35,40,41 Our study demonstrated the analgesic effect of nefopam by validating NK1 receptor attenuation, which may reduce SP and NK1 signaling and lead to decreased nociceptive response.…”
Section: Discussionmentioning
confidence: 60%
“…Neurosteroids are endogenous molecules enriched in the brain that exhibit pleiotropic actions in the central nervous system. Allopregnanolone, a positive GABA A (γ-aminobutyric acid) receptor modulator 6,7 and downstream metabolite of pregnenolone, has known analgesic, [8][9][10][11][12][13][14] neuroprotective, [15][16][17][18][19][20][21] neurotrophic, 18 and anti-inflammatory properties. [22][23][24] Extensive data from preclinical models demonstrate that neurosteroids exhibit pronounced analgesic actions, and data demonstrate that neurosteroids are decreased in the setting of pain symptoms in clinical populations.…”
Section: Introductionmentioning
confidence: 99%